Religiosity, Meaning-Making and the Fear of COVID-19 Affecting Well-Being Among Late Adolescents in Poland: A Moderated Mediation Model - Krok, Dariusz (Journal of religion and health, 2021)
Adolescents have come to be greatly affected by the COVID-19 pandemic and the ensuing containment measures in recent months. The aim of the present study was to examine the relations among religiosity, meaning-making, fear of COVID-19, and subjective well-being within a moderated mediation model. Three hundred and sixteen late adolescents (173 women and 143 men) in Poland volunteered to take part in the study. The results show that meaning-making mediated relationships between religiosity and life satisfaction, religiosity and positive affect, and religiosity and negative affect. In addition, these mediation effects were moderated by the fear of COVID-19. Specifically, the indirect effects were stronger for adolescents with high fear than for those with low fear, which indicates that fear of COVID-19 serves as a ‘warning’ factor.